Canine visceral leishmaniasis in the northern region of the state of Rio Grande do Sul (Research, Society and Development, 2022)
Leishmaniasis is a zoonotic disease caused by the protozoan species Leishmania spp., diagnosed infrequently in dogs from the northern region of Rio Grande do Sul (RS). Because of this, allochthonous cases become important for investigation. The objective of this work is to report a case of visceral leishmaniasis in a canine and to emphasize its clinical, diagnostic and therapeutic aspects. A 3-year-old Pug dog from Araranguá, in the state of Santa Catarina (SC), was treated with a main complaint of hyporexia, prostration, onychogryphosis and pain in the pelvic limbs. The patient had been using immunosuppressants for two months due to the presence of polyarthritis. Clinical examination revealed a skin nodule and an increase in popliteal lymph nodes. Fine-needle cytology was performed at both sites, where amastigote forms of Leishmania spp. The case was notified to Organs competent bodies and serology was performed using the Elisa method to confirm the diagnosis. Treatment with miltefosine, domperidone, allopurinol and Leish Tec® vaccine was instituted. The importance of a thorough anamnesis associated with laboratory tests to screen patients with the disease is highlighted, focusing on the possibility of allochthonous cases being diagnosed in non-endemic regions of Brazil.